Phonological Rhetoric of Submission in the Qur’an: A Stylistic Analysis of the Fifteen Sajdah Verses - Hanifa, Zahra Aulia; Dewi, Dita Puspita; Sopian, Asep (Faculty of Adab and Humanities - Alauddin State Islamic University of Makassar, 2026)
This study examines how the sound system in the verses of sajdah functions not only as beauty, but as a rhetorical device that reinforces the meaning of submission (sujūd). Departing from the Leech–Short stylistic framework and the concept of foregrounding, this study formulates the idea of